Bullying y cyberbullying: intervenciones realizadas en el contexto escolar - Tristão, Laura Aparecida; Iossi Silva, Marta Angelica; De Oliveira, Wanderlei Abadio; Dos Santos, Daniel; Da Silva, Jorge Luiz (Pontificia Universidad Católica del Perú, 2022)
There are gaps concerning the dissemination of school-based antibullying interventions in the Latin American context. For this reason, the objective was to conduct a systematic literature review to analyze the results of initiatives intended to prevent or decrease the occurrence of bullying and cyberbullying. A bibliographic search was conducted in LILACS, PsycINFO, SciELO, SCOPUS, and Web of Science. Only school-based randomized clinical trials conducted were included. Nine studies classified as having high methodological quality were included. This review synthesizes knowledge reported by studies conducted in various countries and clarifies the limitations and contributions of experimental programs focused on students, parents, and school staff, enabling reflections regarding future interventions.

Existen vacíos en el contexto latinoamericano referentes a la divulgación de resultados de intervenciones antibullying en la escuela; así, se pretendió analizar los resultados de acciones para prevención o reducción de la ocurrencia de bullying/cyberbullying. Se trata de revisión sistemática de la literatura. El levantamiento bibliográfico se realizó en las bases de datos LILACS, PsycINFO, SciELO, SCOPUS y Web of Science. Fueron incluidos apenas ensayos clínicos aleatorios en el ambiente escolar. Nueve estudios fueron incluidos en la revisión, que fueron evaluados como siendo de alta calidad metodológica. Esta revisión sintetiza conocimientos obtenidos con estudios realizados en diversos países, esclareciendo limitaciones y contribuciones de programas experimentales dirigidos a estudiantes, padres y equipo escolar, lo que posibilita reflexionar sobre futuras intervenciones.

Il existe des lacunes dans le contexte latino-américain par rapport à la diffusion des résultats des interventions anti-harcèlement dans les écoles. Nous avons analysé les résultats des actions visant à prévenir ou réduire l’apparition de l’intimidation et cyberintimidation (révision systématique de la littérature). L’enquête bibliographique a eu lieu dans les bases de données LILACS, PsycINFO, SciELO, SCOPUS et Web of Science. Seuls les essais cliniques randomisés en milieu scolaire ont été inclus. Au total, neuf études de haute qualité méthodologique ont été incluses dans la révision, synthétisant les connaissances obtenues à partir d’études menées dans plusieurs pays, clarifiant les limites et apports des programmes expérimentaux destinés aux élèves, parents et personnel scolaire. Cela permet des réflexions pour des interventions futures

Existem lacunas no contexto latinoamericano no que se refere à divulgação resultados de intervenções antibullying na escola, desta forma, pretendeu-se analisar os resultados de ações para prevenção ou redução da ocorrência de bullying e cyberbullying. Trata-se de uma revisão sistemática da literatura. O levantamento bibliográfico ocorreu nas bases de dados LILACS, PsycINFO, SciELO, SCOPUS e Web of Science. Foram incluídos apenas ensaios clínicos randomizados no ambiente escolar. Um total de nove estudos foram incluídos na revisão, sendo avaliados como de alta qualidade metodológica. Esta revisão sintetiza conhecimentos obtidos com estudos realizados em diversos países, esclarecendo limitações e contribuições de programas experimentais voltados a estudantes, pais e equipe escolar, o que possibilita reflexões para futuras intervenções.
Bullying and cyberbullying: school-based interventions
Harcèlement et cyberintimidation: interventions réalisées en contexte scolaire
Keywords: Bullying; Cyberbullying; School context; Intervention; Bullying; Cyberbullying; Contexto escolar; Intervención; Intimidation; Harcèlement sur internet; Contexte scolaire; Intervention; Bullying; Cyberbullying; Contexto escolar; Intervenção; https://purl.org/pe-repo/ocde/ford#5.01.00